2013
DOI: 10.1177/1012690213495747
|View full text |Cite
|
Sign up to set email alerts
|

On the door-step of equality: Attitudes toward gay athletes among academy-level footballers

Abstract: In this semi-structured interview research, we investigate the attitudes of 22 academy-level association football (soccer) players who are potentially on the verge of becoming professional athletes. We find that, as a result of these men belonging to a generation holding inclusive attitudes towards homosexuality, independent of whether they maintain contact with gay men, they are unanimously supportive of gay men coming out on their team. Thus, this research supports a growing body of literature suggesting tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
2
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 29 publications
2
68
2
1
Order By: Relevance
“…Homophobia is often used to socialize and police conformity to traditional gender norms (28, 29). Coaches and male peers may view any deviation from traditional gender norms, such as perceived athletic incompetence, as an indicator of being less masculine and thus non-heterosexual (e.g., calling a boy who is not good at football a “fag”) (28-30). Consistent with this finding, one study of high school males in urban Pennsylvania found that those who were engaged in competitive team sports were three times as likely as those not in team sports to express homophobic beliefs (22).…”
mentioning
confidence: 99%
“…Homophobia is often used to socialize and police conformity to traditional gender norms (28, 29). Coaches and male peers may view any deviation from traditional gender norms, such as perceived athletic incompetence, as an indicator of being less masculine and thus non-heterosexual (e.g., calling a boy who is not good at football a “fag”) (28-30). Consistent with this finding, one study of high school males in urban Pennsylvania found that those who were engaged in competitive team sports were three times as likely as those not in team sports to express homophobic beliefs (22).…”
mentioning
confidence: 99%
“…These athletes are able to cry in public, they support each other with emotional concerns and the openly express their bromances (a close intimate same-sex male friendship that often involves exclusive emotional disclosure). Often, the young athletes of today link their Facebook accounts claiming that they are in relationships with their best friends as a symbol of endearment (Anderson, 2013), which is similar to McCormack's (2012) findings which shows close friends greeting one another with expressions such as 'hey boyfriend'.…”
Section: Imt and Sportmentioning
confidence: 61%
“…The softening of masculinities has also allowed athletes to improve their homosocial relations, primarily via emotional openness and physical tactility (Anderson, 2013(Anderson, , 2014Anderson and McCormack, 2014). Emoting is emerging as a key component of inclusive masculinities in times of reduced homohysteria (Anderson, 2014).…”
Section: Imt and Sportmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been particularly in evident in sporting research: Magrath's (2017aMagrath's ( , 2017b) work on young elite soccer players has indicated almost unanimous acceptance of openly gay teammates -irrespective of whether there were gay players on the team (see also Magrath, Anderson, & Roberts, 2015;Roberts, Anderson, & Magrath, 2017). The lack of policing of gendered behaviours has led to a complete renegotiation of the old masculine script in many other settings, too.…”
Section: Eric Andersonmentioning
confidence: 99%